Chemical sand production control: a review of materials, methods and characterization - Xu, Zhenqiang; Shen, Kaixiang; Zhou, Jiawei; Huang, Qisheng; Liu, Pingli; Du, Juan; Wu, Jia (Frontiers in Energy Research, 2024)
Sand production is one of the challenges facing the oil industry. This paper reviews the latest research advances in chemical sand control and aims to provide a reference for related researchers. Firstly, the commonly used chemical sand control materials are introduced. Second, recent advances in chemical sand control are reviewed, including materials, methods, and processes. Third, laboratory methods for sand control research are presented. Finally, the gaps and challenges of chemical sand control materials are pointed out, and possible future directions for chemical sand control methods are envisioned.